STRATEGI BERSAING PADA GELATIK RESIDENCE PALU - Tanwir D G Djuma; Johnny Tanamal; Syamsul Bachri Daeng Parani (Universitas Tadulako, 2015)
PT. Regional Trypillian is a company that is engaged in the development of new houses to prosper the society, especially by providing residence and develop its role in economic development in marketing the residential products and utilization of manpower. The establishment of the company initiated by Mr. Sofyan Hudri since February 15, 2014, starting from an attempt to manage, market, and produce home with investors/landowners. Wren's housing residence consists of 2 types: type 50 and type 90. The purpose of this study is to determine competition faced by Wren Residence in Palu and to examine alternative strategies that can be used by Wren Residence. Data analysis technique used is the SWOT analysis (Strength, Weakness, Opportunity, Threat). Based on the results of SWOT analysis in the form of matrix diagram and IE table, it finds that competitive strategies of Wren Residence is focused on aggressive strategy (growth-oriented strategy) that is suitable with the existing opportunities. PT. Regional Trypillian adalah perusahaan yang bergerak dalam pengembangan rumah baru untuk mencapai kesejahteraan masyarakat, terutama dengan menyediakan tempat tinggal dan mengembangkan perannya dalam pembangunan ekonomi dalam memasarkan produk hunian dan pemanfaatan tenaga kerja. Pembentukan perusahaan yang diprakarsai oleh Bapak Sofyan Hudri sejak 15 Februari 2014 ini, mulai dari usaha mengelola, memasarkan, dan menghasilkan rumah dengan investor / pemilik lahan. Tempat tinggal Wren terdiri dari 2 tipe: tipe 50 dan tipe 90. Tujuan dari penelitian ini adalah untuk mengetahui kompetisi yang dihadapi Wren Residence di Palu dan untuk mengkaji strategi alternatif yang dapat digunakan oleh Wren Residence. Teknik analisis data yang digunakan adalah analisis SWOT (Strength, Weakness, Opportunity, Threat). Berdasarkan hasil analisis SWOT berupa diagram matriks dan tabel IE, maka strategi kompetitif Wren Residence difokuskan pada strategi agresif (strategi berorientasi pertumbuhan) yang sesuai dengan peluang yang ada.